Topiramate Compared to Acetazolamide in Treatment of Idiopathic Intracranial Hypertension - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The efficacy of topiramate in the treatment of idiopathic intracranial hypertension (IIH) was compared to acetazolamide in an open-label study of 40 patients (age range 16-50, median 32 years; male/female ratio 5/35) at Ege University Medical School, Izmir, Turkey.